Determination and improvement of wear and abrasion properties of Glass Reinforced Plastic (GRP) piping for slurry applications - Van der Schyff, A. (Vaal University of Technology, 2014)
Glass Reinforced Plastics (GRP) are composite materials comprising a resin matrix reinforced with glass fibers, and are well known for their excellent corrosion resistance and high strength-to-weight ratios. However, their use in slurry transporting pipes is uncertain because the wear resistance of GRP pipe materials is not well documented due to the difficulty encountered in standardizing mechanical properties of GRP pipes. The aim of this project was to identify the main variables that influence the wear and abrasion properties of GRP pipes and the differences of abrasion properties between the continuous and discontinuous filament wound pipes that are manufactured by Amitech SA. In order to achieve the aim of the project, the mechanisms of wear in ductile and brittle matrix GRP composites were investigated. The Pin-on-disk and Jet-impact tests were identified as the best abrasion tests suited for testing GRP composites. Data collected from these tests indicated that the resin type, curing, additive content and- type, fiber content and manufacturing methods are factors affecting wear resistance. It was further found that hard surfaces provided better resistance to abrasive wear, whereas ductile matrices performed better under erosive wear.
M. Tech. (Department of Metallurgical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Glass Reinforced Plastic (GRP); Composite materials; Abrasive wear; Erosive wear; Glass fibres; Slurry piping; Dissertations, Academic -- South Africa.; Fiber glass-reinforced plastics -- Mechanical properties.; Slurry pipelines.; Glass-reinforced plastics -- Testing.